Design of low to medium rise buildings against external explosions. (Technical note, 2018)
This Technical Note has been prepared as a deliverable of a joint European project funded by the European Union's Research Fund for Coal and Steel (RFCS) research programme under grant agreement number RFSR-CT-2013-00020. The project has also received financial support from the Centre for the Protection of the National Infrastructure in the UK. The objective of the project was to develop design guidelines for low to medium rise steel framed buildings (typically two to five storeys high) to resist explosions caused by industrial accidents where the blast from the explosion impacts the whole (or a large part) of the elevation of the building facing the blast. Explosion tests were performed to quantify the distribution of actions on a building and the explosion response of building components (cladding, connections and floor systems).